Pengaruh Pemberian Kompensasi terhadap Peningkatan Kinerja Karyawan pada Dinas Koperasi dan UMKM Kota Bandung - Rizkia Alia Fauziah; Aminuddin Irfani (UNISBA Press, 2022)
Abstract. This study aims to determine how much influence compensation has on improving employee performance at the Department of Cooperatives and SMEs in Bandung. In this study there are two variables, namely compensation which is the independent variable and employee performance which is the dependent variable. The population taken in this study were all employees of the Bandung City Cooperative and UMKM Service and the sample consisted of 50 respondents. The research method used is descriptive analysis and verification analysis, using data collection techniques with interviews, questionnaires and observations. Determination of respondents was selected using a non-probability sampling technique which does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample using the saturated sampling method. Saturated sampling or another word for census is where all members of the population are sampled. And, the results of this study prove that there is a relationship between compensation and employee performance. Partially compensation has an effect of 59.5% on employee performance, which means that the more employees receive high compensation, the higher the employee's performance will be. Abstrak. Penelitian ini bertujuan untuk mengetahui berapa besar pengaruh pemberian kompensasi terhadap peningkatan kinerja karyawan pada Dinas Koperasi dan UMKM Kota Bandung. Dalam penelitian ini terdapat dua variabel yaitu kompensasi yang menjadi variabel bebas (independent) dan kinerja karyawan yang menjadi variabel terikat (dependen). Populasi yang diambil pada penelitian ini adalah seluruh karyawan Dinas Koperasi dan UMKM Kota Bandung serta sampel yang diambil terdiri dari 50 responden. Metode penelitian yang digunakan ialah analisis deskriptif serta analisis verifikatif, menggunakan teknik pengumpulan data dengan wawancara, kuesioner serta observasi. Penentuan responden dipilih dengan memakai teknik non-probability sampling yang tidak memberi peluang atau kesempatan sama bagi setiap unsur atau anggota populasi untuk dipilih menjadi sampel menggunakan metode sampling jenuh. Sampling jeuh atau kata lain dari sensus ialah dimana seluruh anggota populasi dijadikan sampel. Dan, hasil penelitian ini membuktikan adanya bahwa adanya hubungan antara kompensasi terhadap kinerja karyawan. Secara parsial kompensasi memberikan pengaruh sebesar 59,5% terhadap kinerja karyawan yang artinya semakin karyawan mendapat kompensasi tinggi maka akan meningkatkan kinerja karyawan tersebut.